Analysis of Hindu Teachings Messages Karmaphala and Tri Hita Karana in Pulau Plastik Movie Series (Journal of Comparative Study of Religions, 2024)
Educational documentary film is a visual media tool used to convey certain messages to the audience. One of them is the film series Pulau Plastik by Dandhy Dwi Laksono. In the film, it describes the dangers of plastic for the environment and humans by using the terminology of Hindu teachings, such as Karmaphala and Tri Hita Karana. The purpose of this study is to analyse the meaning of Hindu ecological teachings and also describe how films using religious messages can make the audience understand the teachings themselves while building environmental awareness. This research is a qualitative literature research, using a sociological approach to study the relationship between religion and society, then through descriptive analysis methods to collect related data. The findings of this research show that religious teachings that are often considered transcendent can be grounded using visual media. Hindu ecology is contained in the teachings of Tri Hita Karana and also Karmaphala which explain that the mutual relationship between nature, humans, and God is aimed at achieving happiness and peace.